The Role of Sharia Cooperatives in Increase Welfare Members and Society in the Digital Age - Ginna Novarianti Dwi Putri Pramesti (Journal of Sharia Micro Enterprise and Cooperation, 2024)
Digitalization cooperative Sharia in Indonesia offers potential big in increase welfare economic and social its members, especially in limited areas access service finances. Research This aiming for analyze impact digitalization to welfare member cooperative sharia and society surrounding areas, as well as identify factors success in implementation digital technology. Research use method survey descriptive with approach quantitative, involving 200 members cooperative sharia from various regions that have adopt digital services. Research results show that digitalization cooperative sharia impact significant on increasing income members, efficiency operational, and satisfaction members. In addition, that, digitalization expands inclusion finance, with improvement amount member cooperative by an average of 20-25% in rural areas. However, there are challenges, such as low digital literacy and limitations infrastructure in several area. Implications from study This push importance support government in form training digital literacy and improvement infrastructure in remote areas. Study This conclude that digitalization cooperative sharia play role important in support inclusion finance and well-being members in the digital era. It is hoped that research This can become reference for maker policy and practitioner’s cooperative in optimize potential cooperative sharia through digital innovation.